The legacy of John : second-century reception of the Fourth Gospel - Rasimus, Tuomas. (Novum Testamentum, Supplements, 2010)
This volume investigates the early, second-century reception of the Fourth Gospel. This is an era when its fortunes are surrounded by silence and mystery. It was assumed, until quite recently, that Gnostic and other so-called heterodox groups were the first ones to appreciate this gospel, and hence the mainstream Christians avoided using it until Irenaeus rescued it for the church. Lately, this view has been challenged by several scholars for several reasons. The contributions in this volume, written by leading specialists in their respective fields, offer an approachable, fresh, comprehensive and up-to-date view of the second-century reception of John's Gospel, in a situation where new understandings about various forms of early Christianity and its multiformity have started to emerge.